Retail marketing / Sean Ennis - Ennis, Sean1957-
"Retail Marketing is a new and refreshing text, essential for anyone wanting to get to grips with this important, fast-paced area of marketing today. With a user-friendly structure, this book reflects the very latest in academic thinking and provides a strong focus on customer value, corporate social responsibility and the transformative effect of digital technology. Written especially for European and international students and suitable for both undergraduate and postgraduate students, Retail Marketing addresses the challenges of marketing in the 21st Century. Across the chapters key elements of successful retail marketing, including developments in omni-channel marketing and the importance of a co-ordinated supply chain to a company's value proposition, are considered. Striking a balance between theory and practice, Retail Marketing presents concepts in a clear and comprehensive way with engaging, up-to-date global examples and visual illustrations to help students apply their knowledge to a real world context"